Piezoelectric energy harvesting under free and forced vibrations for different operating conditions - Amine Ben Alaya; Charfeddine Mrad; Férid Kourda (AIMS Energy)
The field of energy harvesting has grown rapidly, with the huge development in low-power devices and the Internet of Things (IoT). With the intent of harvesting electrical energy for self-powered devices, piezoelectric technology is considered. In this study, we proposed several electrical and mechanical improvements to enhance the electrical energy produced through piezoelectricity. To determine the best electrical configuration to harvest piezoelectric energy, three harvesting electric circuits were proposed and tested using a piezoelectric material (PZT-5H) mounted directly on a vibration exciter. The harvested electrical energy by each circuit was determined at different excitation frequencies, from 20 to 50 Hz, with an excitation amplitude of 2 mm. The favorable electric circuit produced approximately 35 μJ of electrical energy at an excitation frequency of 50 Hz. This circuit was subsequently used for the remaining aspects of this work. To enhance the obtained electrical energy, a fixed-free metallic plate was used. First, free vibration was tried, imposing an excitation displacement of different values to the free end of the plate. The plate consisted of different materials: copper, aluminum, and steel. The PZT-5H was mounted at different positions on the plate. The harvested electrical energy was determined for each plate material, each piezoelectric material position, and each excitation displacement. The highest harvested energy was around 6 μJ. Second, forced vibration was tried, imposing an excitation amplitude of 0.5 mm at different excitation frequencies, from 10 to 50 Hz, to the fixed end of the plate. The plate was of different lengths. The highest harvested energy was around 540 μJ. Third, we showed that it is possible to further increase the harvested electrical energy by tuning the plate resonance to 50 Hz. The harvested energy was then around 1010 μJ. The obtained results allowed optimizing piezoelectric energy harvesting toward supplying low-power devices for different applications.